THE OPTIMISATION OF LIFE CYCLE OF GFRP PRODUCT - (:unkn) unknown (TECHNICAL UNIV CLUJ-NAPOCA, 2016)
Given the technological possibilities of current century, many products can be manufactured easily in terms of functional and geometrical product specifications. However, it is not that easy finding customers in the market. In addition to functional properties, a product has also to be cost and energy efficient and environmental-friendly in order to survive within the context of industry. Under today's competitive circumstances, energy saving and efficiency is the most desired property in many sectors. It is a current perspective to select materials which are lighter than metallic materials but also as durable as in terms of mechanical strength, in addition to design aspects. In the light of this perspective, composite materials have been used widespread in many industry fields. Therefore, a preferred type of composite in automotive, aviation, marine and wind power plant is glass fibre reinforced plastic materials. These materials are classified as thermosetting and thermoplastic, according to the types of used resin. Thermosets cannot be used again in manufacturing of other products. When it is considered, thermosets are not considered as environmental-friendly products. In this study, application areas of GFRP materials, and their advantageous sides in terms of energy saving, and disadvantageous sides as not being environmental friendly are evaluated. Realisation of manufacturing from these materials as both energy and environmental-friendly is analysed.
Keywords: Glass Fiber Reinforced Plastic (GFRP); Recycling; Environmental Management; SURFACE QUALITY